Essential Role of Serum Calcium for Muscle Strength in Football Athletes. (March 2017) - Yusni,; Amiruddin,; Purba, A; Tarigan, B
Abstract: Exercise increases the reabsorption of calcium from bones and inadequate intake of calcium resulting in hypocalcaemia. Hypocalcaemia is one of the factors causing the decline in leg muscle strength in athletes. The purpose of this study was to analysis the relationship of serum calcium levels and leg muscle strength in football athletes. The research subjects were 22 junior football athletes, male, age 12-17. The study design was an observational laboratory. Serum calcium levels were measured by using O-cresolphthalein complexone and leg muscle strength was measured by using a dynamometer leg. Data obtained were analysed by using Pearson correlation test and simple linear regression analysis (p<0.05). The results of Pearson correlation test (r) showed r=0.25; p=0.50, indicated that there is a low correlation between the serum calcium level and leg muscle strength, but not statistically significant. The results of simple linear regression analysis showed that the increase of serum calcium level by 2 mg/DL resulted in the increase of leg muscle strength about 13.07 kg. It can be concluded that serum calcium levels were positively associated with lower leg muscles strength, however, a decrease in serum calcium levels was not followed by a decrease in leg muscle strength in football athletes.